Influence of nanoscale order–disorder transitions on the magnetic properties of Heusler compounds for spintronics. Issue 18 (2nd May 2017) - Karel, J.; Fischer, J. E.; Fabbrici, S.; Pippel, E.; Werner, P.; Vinicius Castergnaro, M.; Adler, P.; Ouardi, S.; Balke, B.; Fecher, G. H.; Morais, J.; Albertini, F.; et al.
Abstract : Modifications in nanoscale chemical order can tune the magnetic properties of Co2 FeSi x Al1− x, indicating disorder as a potential engineering tool. Abstract : Modifications in nanoscale chemical order are used to tune the magnetic properties, namely T C, of Co2 FeSi x Al1− x (0 < x < 1). High-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) with Z-contrast reveals nanoscale regions of L21 order within a B2 matrix in the off-stoichiometry samples. Perhaps surprisingly, the latter, more chemically disordered structure, exhibits a higher T C . Upon annealing, the off-stoichiometry samples become more homogeneous with the fraction of L21 order decreasing. The short-range order was also investigated using X-ray absorption fine structure (XAFS) measurements at the Co and Fe K edges. Since the local atomic environments of Co atoms in the L21 and B2 structures are identical, the features presented in the Co K edge XAFS data are the same in both cases. By contrast, the L21 and B2 structures exhibit different signatures at the Fe K edge owing to the different chemical environments. Fitting of these spectra confirms the nanoscale chemical disorder observed by HAADF-STEM and the expected role this disorder plays on T C . Our results point to a methodology that might be extended to modify the magnetic and electronic properties of any Heusler compound; chemical disorder can be an engineering tool to realize highly tailored properties.